LEGAL DILEMMAS IN RELEASING INDONESIA’S POLITICAL PRISONERS - Pascoe, Daniel (Indonesia Law Review, 2017)
In May 2015, in an effort to foster peace in the restive Papua and West Papua Provinces, Indonesian President Joko ‘Jokowi’ Widodo granted clemency to five political prisoners, releasing them from sentences ranging from 20 years to life. The president also stated that there would be ‘a follow-up granting clemency or amnesty to other [political prisoners] in other regions’ (Jakarta Post, 10 May 2015). However, with up to 50 political prisoners still incarcerated in prisons around Indonesia (mostly Papuan and Moluccan separatists), Jokowi’s selective release policy faces several legal and political obstacles. This article outlines the various options open to Jokowi in facilitating future political prisoner releases (including amnesty, clemency, remissions and conditional release), the advantages and disadvantages of each, before suggesting an acceptable way forward for all parties.